ANALYSIS OF THE FACTORS FOR CHANGING THE FOREIGN POLICY OF BRITISH IMMIGRATION TO A POINTS-BASED IMMIGRATION SYSTEM - Lestari, Tina Adelia; Perbawani, Firsty Chintya Laksmi (Program Studi Sosiologi Universitas Malikussaleh, 2025)
This study aims to determine the reasons why the UK changed its immigration foreign policy. This study will explain the factors that drove the change in UK immigration policy to the Points-Based Immigration System. The research method used in this study is explanatory qualitative. This article is compiled by collecting data from books, journal articles, official government websites, and credible articles related to the topic being analyzed. After officially leaving the European Union, the UK stopped the Free Movement policy and replaced it with a new immigration policy based on points, namely the Points-Based Immigration System. This new policy, which is stricter and under the full control of the British government, is expected to reduce the high number of immigrants in the UK. After being bound by EU policies for so long, the UK is finally free to implement its own policies that are in accordance with its national interests. The findings show that changes in UK immigration foreign policy are driven by domestic factors in the form of bureaucracy, public opinion, media, interest groups, and political parties, as well as international factors in the form of global factors, regional factors, bilateral relations, and non-state actors.